Interpersonal Communication of Vaporista With Consumers in Building Consumer Trust at AMW Vapestore Samarinda - Asih, Nur; Purwanti , Silviana; Ibrizah, Ziya; Kristian, Dony (CV. Publikasi Indonesia, 2025)
This qualitative study examines how interpersonal communication between vaporistas (vape shop frontline staff) and consumers builds trust at AMW Vapestore Samarinda, Indonesia. Using social penetration theory by Altman and Taylor (1973), the research explores five stages of relationship development: orientation, exploratory affective, affective, stable, and depenetration. Through in-depth interviews with vaporistas and regular customers who visited at least five times, findings reveal that trust building begins with simple conversations during the orientation stage, progresses through gradual self-disclosure and emotional expression, and culminates in stable relationships characterized by mutual openness and predictability. Vaporistas demonstrate customer service excellence by actively providing product information, showing empathy, and maintaining supportive attitudes. The study confirms that interpersonal communication significantly influences consumer trust, with successful relationships reaching the stable stage where personal connections transcend transactional interactions. However, conflicts can lead to relationship deterioration. The research contributes to understanding frontline communication strategies in the vape retail industry and provides practical implications for employee training and customer relationship management.